The non-high-density lipoprotein cholesterol to high-density lipoprotein cholesterol ratio is associated with early onset type 2 diabetes with NAFLD: a cross-sectional study in China - Wu, Nini; Ni, Yingqun; Huang, Rilong; Wang, Junhua; Li, Meimei; Hu, Haiying; Zhang, Yuanyuan; Li, Juyi; Zhang, Jinjun (Frontiers in Nutrition, 2025)
BackgroundThe non-high-density lipoprotein cholesterol to high-density lipoprotein cholesterol ratio (NHHR) is a novel composite lipid biomarker associated with metabolic diseases. This study aims to explore the potential relationship between early-onset type 2 diabetes mellitus combined with NAFLD and NHHR.MethodsA total of 1,158 patients with type 2 diabetes were enrolled and categorized by age at onset into the early-onset type 2 diabetes (EOT2D) group (260 cases, <40 years) and the late-onset type 2 diabetes (LOT2D) group (898 cases, ≥40 years). The EOT2D group was further subdivided into those with NAFLD (136 cases) and those without NAFLD (124 cases). Multivariate logistic regression assessed the association between NHHR and EOT2D, as well as EOT2D combined with NAFLD. Additionally, we employed subgroup analysis, interaction analysis, smoothing curve fitting, and receiver operating characteristic curve analysis to further explore risk factors for EOT2D and EOT2D combined with NAFLD.ResultsThis cross-sectional study included 260 EOT2D patients and 898 LOT2D patients. After adjusting for confounding factors, the study found that for every 1-unit increase in NHHR, the risk of EOT2D increased by 22% (OR = 1.22, 95% CI: 1.05–1.42), and the risk of EOT2D with NAFLD increased by 41% (OR = 1.41, 95% CI: 1.01–1.98). The AUC for diagnosing EOT2D with NAFLD using NHHR was 0.658 (95% CI: 0.592–0.724), with an optimal cutoff of 3.105 (sensitivity 77.21%, specificity 50.00%).ConclusionOur study suggests that NHHR is a risk factor for EOT2D and EOT2D combined with NAFLD, serving as a reference indicator for screening this high-risk population.